2022
DOI: 10.26434/chemrxiv-2022-2g6m6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of an orally bioavailable and selective PKMYT1 inhibitor RP-6306

Abstract: PKMYT1 is an important regulator of CDK1 phosphorylation and is a compelling therapeutic target for the treatment of certain types of DNA damage response cancers due to its established synthetic lethal relationship with CCNE1 amplification. To date, no selective inhibitors have been reported for this kinase that would allow for investigation of the pharmacological role of PKMYT1 in the treatment of cancer. To address this need we conducted a focused screening effort that identified compound 1 as a weak PKMYT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Among the inhibitors identified as hits, the 3-phenol compound [dubbed 1 in the reference paper (Figure 18B)] appears to be an excellent lead structure, particularly considering the 50−60-fold selectivity observed over the highly homologous enzyme WEE1. 180 SBDD supported by multiple cocrystal structures enabled the optimization of keys properties, including PKMYT1 cell-based potency and kinase activity. The medicinal chemistry campaign took a fortunate turn with the introduction of a dimethylphe-nol substituent into the azaindole core.…”
Section: Plk1mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the inhibitors identified as hits, the 3-phenol compound [dubbed 1 in the reference paper (Figure 18B)] appears to be an excellent lead structure, particularly considering the 50−60-fold selectivity observed over the highly homologous enzyme WEE1. 180 SBDD supported by multiple cocrystal structures enabled the optimization of keys properties, including PKMYT1 cell-based potency and kinase activity. The medicinal chemistry campaign took a fortunate turn with the introduction of a dimethylphe-nol substituent into the azaindole core.…”
Section: Plk1mentioning
confidence: 99%
“…RP-6306 showed nanomolar cell-based potency against PKMYT1, excellent selectivity toward a panel of kinases, including WEE1, favorable PK, and ultimately efficacy in an ovarian CCNE1-amplified xenograft model (Table 6). 180 The first-in-class clinical candidate RP-6306 reported by Repare Therapeutics is currently being evaluated in phase 1 clinical trials for the treatment of various solid tumors alone or in combination therapies with FOLFIRI (NCT05147350), gemcitabine (NCT05147272), and the ATR selective inhibitor RP-3500 (NCT04855656). 180 Most recently, Repare Therapeutics has partnered with Debiopharm to explore SL combination of PKMYT1 and WEE1 in cancer.…”
Section: Plk1mentioning
confidence: 99%
See 1 more Smart Citation
“…A patent (US11332473B2) 37 claimed a set of substituted pyrazolo [3,4-d]pyrimidines as Wee1 inhibitors, in which compound "1.40" is active against PKMYT1 with an IC50 of 0.121 μM. In 2022, Szychowski et al 38 reported the discovery of the first potent, selective, and orally bioavailable PKMYT1 inhibitor, RP-6306. This inhibitor shows an IC50 of 0.002 μM, and high selectivity observed over the highly homologous enzyme Wee1.…”
Section: Kinomemeta-aided Discovery Of Kinase Inhibitorsmentioning
confidence: 99%